Psychological factors of secondary school graduates’ hardiness - Liudmyla Serdiuk; Ivan Danyliuk; Olena Chykhantsova (Social Welfare: Interdisciplinary Approach)
The article examines the personal qualities of secondary school graduates that determine their hardiness at their professional self-determination. The modern approaches defining hardiness essence and factors, and peculiarities of its development are analyzed. The factors contributing to the enhancement of an individual’s hardiness in the situation of professional self-determination are considered.